Midlife experiences of Filipino women issues and challenges - Abiva, Thelma Gail G. 1972- (2007)
This study was undertaken to explore the occurrence of midlife in the Philippine setting and how Filipino women define the word "midlife". It used a grounded theory approach (GTA) taking into account the feminist perspective. Data were gathered by conducting interviews and focus group discussions (FGD). The study focused on Filipino women 39 to 49 years of age, married or single, from middle or low income groups in the Metro Manila area. The study showed that the women respondents considered 35 to 60 years old as the age range of midlife in the Philippines, and that the concept of midlife depended on their perception of life and their experiences in coping with midlife. The study concluded with recommendation for further research, dissemination of information, and introduction of feminism and women empowerment to the public.